Risk factors for injuries due to the 1990 earthquake in Luzon, Philippines. - Roces, M. C. (World Health Organization, 1992)
On 16 July 1990, an earthquake measuring 7.7 on the Richter scale struck the island of Luzon, Philippines. A case-control study was carried out to identify the risk factors for earthquake-related injuries and at the same time observations were made on the rescue efforts. Being hit by falling objects was the leading cause of injury (34%). Those injured during the tremor were more likely to have been inside buildings constructed of concrete or mixed materials (odds ratio, 2.6; 95% confidence interval (CI), 1.7-4.1) and to have been on the middle floors of multistorey buildings (odds ratio, 3.4; 95% CI, 2.2-5.5). Leaving a building during the earthquake was a protective behaviour (odds ratio, 0.3; 95% CI, 0.2-0.8). Of the 235 survivors who were trapped and rescued alive from the rubble, 99% were rescued within 48 hours of the impact of the tremor. These findings should prove useful in developing seismic safety codes. People should be taught proper evasive actions to take during earthquakes, and training in basic first aid and methods of rescue should be an integral part of community preparedness programmes.